Symbolic Economy And City Branding: Visual Semiotics Of Batam's Instagram Promotions - Taufiqqurrachman Taufiqqurrachman; Suyanto Suyanto; Ringgo Eldapi Yozani; Jamhur Poti (Interaksi: Jurnal Ilmu Komunikasi, 2026)
Existing research has examined the role of Instagram in city branding and tourism promotion, yet the formation of city identity within the symbolic economy, especially through visual meaning-making, remains underexplored. Drawing on the symbolic economy perspective, this study investigates the construction of Batam’s destination brand. The study analyzed 470 posts from the official Instagram account of the Batam City Tourism and Culture Office using a qualitative visual semiotic approach. Peirce’s semiotic framework and Cohen’s authenticity dimensions were used to interpret representations of Malay culture. The findings show that Malay cultural elements function as symbolic resources expressed through the dimensions of origins, creativity, and genuineness. The study further suggests that social media contributes to destination promotion while functioning as a space where cultural meanings are produced and local culture acquires symbolic value in city-branding practices.